A touch of jen eaudiobook - Morgan, Beth (2021)
A young couple's toxic Instagram crush spins out of control and unleashes a sinister creature in this twisted, viciously funny, "bananas good" story (Carmen Maria Machado). "Um, holy shit...This novel will be the most fun you'll have this summer." —Emily Temple, Literary Hub Remy and Alicia, a couple of insecure service workers, are not particularly happy together. But they are bound by a shared obsession with Jen, a beautiful former co-worker of Remy's who now seems to be following her bliss as a globe-trotting jewelry designer. In and outside the bedroom, Remy and Alicia's entire relationship revolves around fantasies of Jen, whose every Instagram caption, outfit, and new age mantra they know by heart. Imagine their confused excitement when they run into Jen, in the flesh, and she invites them on a surfing trip to the Hamptons with her wealthy boyfriend and their group. Once there, Remy and Alicia try (a little too hard) to fit into Jen's exalted social circle, but violent desire and class resentment bubble beneath the surface of this beachside paradise, threatening to erupt. As small disturbances escalate into outright horror, we find ourselves tumbling with Remy and Alicia into an uncanny alternate reality, one shaped by their most unspeakable, deviant, and intoxicating fantasies. Is this what "self-actualization" looks like? Part millennial social comedy, part psychedelic horror, and all wildly entertaining, A Touch of Jen is a sly, unflinching examination of the hidden drives that lurk just outside the frame of our carefully curated selves.